Psychological aspects of security and privacy in the digital environment - SPRAVTSEVA, Kateryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. In the era of rapid digitalization and the increase in social network users to 5.5 billion people (67.1 % of the global population), safeguarding personal privacy in the digital realm has become increasingly significant. According to Pew Research Center (2024), 79 % of users are concerned about personal data protection, while privacy violations are showing a worrying upward trend. The study aims to conduct a comprehensive analysis of the psychological mechanisms of privacy management in social networks and to develop evidence-based strategies for safeguarding users’ psychological well-being. Methods. The research employes a combination of systemic and person-centered approaches along with social cognitive theory. A diverse range of theoretical methods (systematic literature review, meta-analysis of empirical research, conceptual modeling) and empirical methods (psychodiagnostic techniques, neuropsychological studies, longitudinal observations) were utilized. A meta-analysis of 166 studies, encompassing over 75,000 participants, was conducted. Results. The existence of the "privacy paradox" — the gap between stated privacy concerns and actual user behavior — has been empirically verified. A significant correlation was found between privacy violations and a decline in psychological well-being, indicated by increased levels of anxiety and depressive symptoms. Neuropsychological studies revealed the activation of specific brain structures during decision-making related to information disclosure. The research also examined the digital resilience scale and identified the primary manipulative strategies employed in social networks: persuasion (33 %), agitation (17 %), and information distortion (15 %). Conclusions. The need for a comprehensive approach to privacy protection that combines the development of digital competence, media literacy, and psychological resilience has been established. The effectiveness of a media psychological support system through interconnected areas of media analytics, media therapy, and media education has been substantiated. The research findings provide a theoretical basis for designing psychological support programs for social network users and enhancing privacy protection systems.